IDENTIFYING THE MYTH OF THE BANYAN TREE CIRCULATING IN THE COMMUNITY - Neva Vioretha (SEMESTA: Journal of Science Education and Teaching, 2022)
Banyan (Ficus Benjamina l.) Is a type of tree that is found in Indonesia. Banyan tree grows with hanging roots that grow bigger and bigger. This paper identifies the air content around the banyan tree (Ficus Benjamina l.). The results of observations show that there are several compounds contained in the banyan tree. In the midst of the public circulated rumors that say that many mystical things that make the banyan tree often sacred and feared. One of the rumors circulating is not being able to sleep under a banyan tree because it could die. The conclusion of this observation is that the public's knowledge is correct, that the prohibition of sleep under the Banyan tree can cause fatal consequences, namely death. It's just that people consider it related to mystical things associated with the existence of supernatural beings. Apparently the assumption was wrong after being studied scientifically. These observations reveal that the banyan tree's hanging roots produce CO2 gas which is toxic to the human body. If the CO2 gas is inhaled by humans and then mixed with the bloodstream, the blood hemoglobin can bind more strongly with CO2 and is toxic. Blood flow will flow to the brain and interfere with the work of the brain, so the fatal result that can occur is death.